A novel absorption-based enclosed heat pump dryer with combining liquid desiccant dehumidification and mechanical vapor recompression: Case study and performance evaluation. (July 2022) - Su, Wei; Ma, Dongxu; Lu, Zhifei; Jiang, Weixue; Wang, Feng; Xiaosong, Zhang
Abstract: Drying process is ubiquitous and represents one of the most energy-intensive processes in varieties of agricultural, residential and industrial applications. As an effective heat recovery technology, the heat pump has recently been applied in various drying systems to provide heating and cooling, exhibiting good energy-saving potentials. However, existing condensing-based heat pump drying (HPD) systems require to significantly cool humid air for dehumidification, deteriorating energy efficiency. In this paper, an absorption-based enclosed HPD system is proposed to achieve total waste heat recovery by combining liquid desiccant dehumidification and mechanical vapor recompression. This study focuses on a comprehensive thermodynamic modeling and performance evaluation of proposed absorption-based HPD system. Analysis results indicate that the proposed system can deliver an energy utilization ratio of 4.54 and specific moisture extraction rate of 4.25 kg/kWh under design operation conditions, which is 18.7% and 18.5% higher than the traditional HPD system, respectively. Additionally, an economic analysis is adopted to appraise the economic performance, and obtained results show that the annual investment and maintenance cost rates of proposed system increases by 5.05%, but the annual operation cost rate is reduced by 19.94% compared to the reference system. The payback period is around 18.5monthes with a project life cycle of 20 years, which indicates that the project is profitable. Graphical abstract: Image 1